We fought tooth and toenail: exploring the dynamics of romantic relationships among sex offenders who have desisted - Lytle, Robert (Criminal justice studies, 2017)
Recent research into desistance processes in criminology has identified various explanations and factors in the decision to end criminal careers. One of these life events, shown to generally promote desistance, has been the presence of a romantic relationship. In this study, we argue that research into the role of romantic relationships in sex crime desistance has overlooked the context of romantic relationships, especially pertaining to the quality of relationships. We analyzed interviews with 25 desisting sex offenders, who have returned to the community, to determine how relationship quality varies over time for desisters. Also, we identified themes in the romantic relationships of desisters relative to their conviction (i.e. pre-conviction vs. post-conviction). These findings provide early evidence of the variation in relationship quality amongst sex crime desisters, as well as the impact that relationship quality has on desisters. We conclude that future research in sex crime desistance processes should include relationship quality, not just the presence of a romantic relationship.